Identification of alpha-substituted acylamines as novel, potent, and orally active mGluR5 negative allosteric modulators. Issue 16 (15th August 2015) - Yoshikawa, Keita; Ohyama, Tomofumi; Takahashi, Eiki; Numajiri, Yoshitaka; Konno, Mitsuhiro; Moriyama, Masaki; Takemi, Natsumi; Kunita, Kana; Nishimura, Kazumi; Hayashi, Ryoji
Graphical abstract: Abstract: This Letter describes the identification of a series of novel non-acetylenic mGluR5 negative allosteric modulators based on the alpha-substituted acylamine structure. An initial structure–activity relationship study suggested that ( R )-19b and ( R )-19j might have good in vitro activity. When administered orally, these compounds were found to have an anxiolytic-like effect in a mouse model of stress-induced hyperthermia.